Therapeutic use of medicinal plants and their extracts. Volume 1, - Alamgir, A. N. M., 1950- (Springer, 2017)
This volume focuses on the importance of therapeutically active compounds of natural origin. Natural materials from plants, microbes, animals, marine organisms and minerals are important sources of modern drugs. Beginning with two chapters on the development and definition of the interdisciplinary field of pharmacognosy, the volume offers up-to-date information on natural and biosynthetic sources of drugs, classification of crude drugs, pharmacognosical botany, examples of medical application, WHÓs guidelines and intellectual property rights for herbal products.
Includes index.
Keywords: Pharmacognosy.; Materia medica, Vegetable.; Medicinal plants.; elektronické knihy; electronic books